141k views
3 votes
Solve for a
a(x-3)^2 -1

User N S
by
5.4k points

2 Answers

3 votes

A=1x-3^2 :)))))))))))))))))))))))))

User DavidNg
by
4.7k points
3 votes

Hello from MrBillDoesMath!

Answer:

a = 1/ (x-3)^2, x <> 3, a > 0

Discussion:

Solve

a(x-3)^2 -1 = 0 => add 1 to both sides

a(x-3)^2 = 1 => divide both sides by (x-3)^2

a = 1/ (x-3)^2

Note: the above solution assumes that x <> 3 ( as we cant't divide by zero) and that a > 0. That is, there is NO solution to the equation is a < 0 as

a = 1/ (x-3)^2 and 1/ (x-3)^2 > 0.

Thank you,

MrB

User Maddogandnoriko
by
5.6k points